Studi Pemahaman Aturan Etika dalam Kode Etik Akuntan: Simulasian Etika Pengauditan - Rustiana - (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2009)
This paper is to investigate ability of accounting student about code of conduct accounting ethics. The definition of ethics is the philosophical study of morality, and, accordingly, morality is clearly identified as the characteristic subject matter of ethic. We use ten scenarios concerning ethical dilemmas in auditing. Data was drawn from a sample of 78 accounting students enrolled in accounting seminar and auditing 2 of Atma Jaya Yogyakarta University. Data collection method is used by a personally questionnaires survey. Data were analysed by qualitative technique. The results show that accounting students have good ability to learn about ethical dilemmas in auditing. The implications of the study are to increasing content of ethic in accounting curricula.